Fusarium mycotoxins in beer production: Characteristics, toxicity, incidence, legislation, and control strategies (Scientia Agropecuaria, 2020)
Beer is a worldwide known alcoholic beverage due to many social and economic reasons and therefore the brewing market is expanding. Because of this, the variety of beers with varied organoleptic characteristics and different compositions was increased using different adjuncts like wheat, rice, corn, among others. However, these adjuncts are targets for numerous Fusarium mycotoxins - mainly deoxynivalenol, zearalenone and fumonisins, these may cause toxic effects to animals and humans. These toxins are also implicated in economic losses, due to worldwide regulations applied for unprocessed and processed food products. Currently, the limits for several mycotoxins have been established for the raw materials involved in brewing, however, there is no specific regulation for mycotoxin contamination in beer; therefore it is essential to apply control measures for the presence of Fusarium mycotoxins during the beer processing.
Keywords: beer; mycotoxins; Deoxynivalenol; Fumonisins; Zearalenone.